2021
DOI: 10.1111/cpf.12687
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery longitudinal wall motion alterations associated with metabolic syndrome and insulin resistance

Abstract: Background and aims: Our objective was to study relationships between the new biomarker of vascular health, carotid artery longitudinal wall motion (CALM) and metabolic syndrome (MetS). Methods: Carotid ultrasound and assessment of MetS and its components were performed with 281 subjects aged 30-45 years. In the longitudinal motion analysis, the amplitude of motion and the antegrade-oriented and retrograde-oriented components of motion between the intima-media complex and adventitial layer of the common caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The different patterns raise the question of whether the longitudinal motion might prove a valuable marker for future risk of cardiovascular disease Cinthio et al, 2006;Yli-Ollila et al, 2013;Zahnd et al, 2015;Zahnd, Boussel, Marion, et al, 2011). That this might be the case is supported by recent studies (Taivainen et al, 2017(Taivainen et al, , 2018(Taivainen et al, , 2021. Furthermore, previous studies have reported that the amplitude of the longitudinal displacement of the arterial wall is reduced in patients with carotid plaques, suspected coronary artery disease, Type 2 diabetes Zahnd, Boussel, Marion, et al, 2011), and periodontal disease (Zahnd et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…The different patterns raise the question of whether the longitudinal motion might prove a valuable marker for future risk of cardiovascular disease Cinthio et al, 2006;Yli-Ollila et al, 2013;Zahnd et al, 2015;Zahnd, Boussel, Marion, et al, 2011). That this might be the case is supported by recent studies (Taivainen et al, 2017(Taivainen et al, , 2018(Taivainen et al, , 2021. Furthermore, previous studies have reported that the amplitude of the longitudinal displacement of the arterial wall is reduced in patients with carotid plaques, suspected coronary artery disease, Type 2 diabetes Zahnd, Boussel, Marion, et al, 2011), and periodontal disease (Zahnd et al, 2012).…”
Section: Introductionmentioning
confidence: 89%